52.9k views
3 votes
Please explain I just started learning this

Please explain I just started learning this-example-1

1 Answer

6 votes

Answer:

x=5

y=7

Explanation:

y = x+2 so plug that in the next equation as y

so it be --> 5x+(-4)(x+2)= -3 now use distributive property

(-4 times x)+(-4 times 2)= -4x+-8 replug that back in

5x-4x+-8 = -3 subtract your x

1x = x so ---> x+-8 = -3 now to get rid of -8 we have to add 8 to it

x= -3 but whatever you do to one side u do to the other so u have to add 8 to -3---> so it be x=5

now take that x=5 and plug it in to your first eqaiuton to get y

y=5+2 ---> y =7

User Blackdad
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.